2004
DOI: 10.2190/tjej-k6ge-auav-eeyc
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Theory of Successful Intelligence to Psychotherapy Training and Practice

Abstract: The theory of successful intelligence developed and tested by Robert Sternberg attempts to predict success in life across analytical, creative, and practical dimensions. This article presents the theory of successful intelligence as a useful framework for incorporating various psychotherapy techniques. Application of the theory has effectively trained teachers to enhance important skills in normally functioning children and adolescents, as well as adults in real world settings. Presumably it can be taught to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Regardless of assessment types, students taught by TSI training outperform those educated by traditional teaching methods (Sternberg, Torff, & Grigorenko, 1998). TSI is usually applied in four ways: examining the relationship between triarchic abilities and academic achievement (Ekinci, 2014), assessing triarchic abilities for entry-level behavior in placement tests relative to scholastic aptitude tests (Stemler, Grigorenko, Jarvin, & Sternberg, 2006;Sternberg, 2006), implementing TSI techniques in psychotherapy training, and practice to aid depressed clients (Kaufman & Singer, 2003 (Malekpour, Shooshtari, Abedi, & Ghamarani, 2016) and academic hope-and reduces academic stress (Samavatian, Latifi, & Abedi, 2014). The principles of TSI have been applied to improve socioemotional outcomes such as motivation, attitude, and perception (Khakpooor, Abedi, & Manshaee, 2019;Zadeh, Abedi, Yousefi, & Aghababaei, 2014).…”
Section: Triarchic Instruction (Theory Of Successful Intelligence Training)mentioning
confidence: 99%
“…Regardless of assessment types, students taught by TSI training outperform those educated by traditional teaching methods (Sternberg, Torff, & Grigorenko, 1998). TSI is usually applied in four ways: examining the relationship between triarchic abilities and academic achievement (Ekinci, 2014), assessing triarchic abilities for entry-level behavior in placement tests relative to scholastic aptitude tests (Stemler, Grigorenko, Jarvin, & Sternberg, 2006;Sternberg, 2006), implementing TSI techniques in psychotherapy training, and practice to aid depressed clients (Kaufman & Singer, 2003 (Malekpour, Shooshtari, Abedi, & Ghamarani, 2016) and academic hope-and reduces academic stress (Samavatian, Latifi, & Abedi, 2014). The principles of TSI have been applied to improve socioemotional outcomes such as motivation, attitude, and perception (Khakpooor, Abedi, & Manshaee, 2019;Zadeh, Abedi, Yousefi, & Aghababaei, 2014).…”
Section: Triarchic Instruction (Theory Of Successful Intelligence Training)mentioning
confidence: 99%
“…The successful intelligence theory implies to a classroom teacher that he/she is aware of the fact that intelligence is predictive not only of the school achievement and success but also life beyond school (Hunt, 2008;Kaufman & Singer 2004). Recent studies (Gates et al, 2016;Lippman Ryberb, Caney & Moore, 2015;Sternberg, 2003) have shown that the predictive measure of the quality of a person's success cannot be limited to his/her memory or analytical skills.…”
Section: The Theory Of Successful Intelligencementioning
confidence: 99%
“…Cattell's (1971), advanced a hierarchical model of two general subfactors of intelligence namely fluid intelligence and crystallised intelligence; Sternberg's (1982) theory of successful intelligence and; Gardner's (1983) theory of multiple intelligence. Kaufman & Singer (2004) have argued that the intelligence theories after the Spearman's (1904) general intelligence theory have considerably advanced the developments in the intelligence theory, assessment and research. Similarly, Otaciuoglu (2016) has argued that learners do not attribute success to the same factors.…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of the psychometric approach over intelligence has declined dramatically since the beginning of the 1970s (Gardner, Csikszentmihalyi & Damon, 2001). Important movements have been witnessed in intelligence theories, research and measurements which point out multiple features of mental capacity predicting individuals' both academic success and life-long skills (Kaufman & Singer, 2004). Contemporary intelligence theories view traditional notion of intelligence as the competence of adaptation to the environment to be defective (Delgoshaei & Delavari, 2012).…”
Section: Introductionmentioning
confidence: 99%